Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

\begin{bmatrix} 1 & 0 & 0 & 0 & 0 & a \\ 0 & 1 & 0 & 0 & a & 0 \\0 & 0 & 1 & a & 0 & a \\0 & 0 & a & 1 & 0 & a \\0 & a & 0 & 0 & 1 & 0 \\a & 0 & 0 & 0 & 0 & 1 \\ \end{bmatrix}

Thanks

share|cite|improve this question
up vote 16 down vote accepted

We have the matrix

$$A= \begin{bmatrix} 1 & 0 & 0 & 0 & 0 & a \\ 0 & 1 & 0 & 0 & a & 0 \\0 & 0 & 1 & a & 0 & a \\0 & 0 & a & 1 & 0 & a \\0 & a & 0 & 0 & 1 & 0 \\a & 0 & 0 & 0 & 0 & 1 \\ \end{bmatrix}$$

Elininating the $a$s below the diagonal by adding multiples of the first, second and third line of $A$, we obtain the upper triangular matrix $A'$:

$$A'= \begin{bmatrix} 1 & 0 & 0 & 0 & 0 & a \\ 0 & 1 & 0 & 0 & a & 0 \\0 & 0 & 1 & a & 0 & a \\0 & 0 & 0 & 1-a^2 & 0 & a-a^2 \\0 & 0 & 0 & 0 & 1-a^2 & 0 \\0 & 0 & 0 & 0 & 0 & 1-a^2 \\ \end{bmatrix}$$

Since adding a mulitple of a row to another row does not alter the determinant, we can say that $\det(A) = \det(A')$. Furthermore, the determinant of an upper triangular matrix is the product of its diagonal entries. Thus, we have:

$$\det(A) = \det(A') = (1-a^2)^3$$

Alternatively, eliminate the $a$s above the diagonal by adding multiples of the fourth, fifth and sixth row. The determinant of a lower triangular matrix can be obtained in the same way.

share|cite|improve this answer

Partition the matrix into blocks $\begin{bmatrix}A&B\\C&D\end{bmatrix}$, where

$A = \begin{bmatrix}1&0&0\\0&1&0\\0&0&1\end{bmatrix}$, $B = \begin{bmatrix}0&0&a\\0&a&0\\a&0&a\end{bmatrix}$, $C = \begin{bmatrix}0&0&a\\0&a&0\\a&0&0\end{bmatrix}$, $D = \begin{bmatrix}1&0&a\\0&1&0\\0&0&1\end{bmatrix}$.

The block matrix determinant formula states that $\det \begin{bmatrix}A&B\\C&D\end{bmatrix} = \det(A)\det(D-CA^{-1}B)$.

Trivially, $A = I_3$ is the $3 \times 3$ identity matrix, so $\det(A) = 1$. Also, $A^{-1} = I_3$.

Thus, $D-CA^{-1}B = D-CB$ $= \begin{bmatrix}1&0&a\\0&1&0\\0&0&1\end{bmatrix} - \begin{bmatrix}0&0&a\\0&a&0\\a&0&0\end{bmatrix}\begin{bmatrix}0&0&a\\0&a&0\\a&0&a\end{bmatrix}$ $= \begin{bmatrix}1&0&a\\0&1&0\\0&0&1\end{bmatrix} - \begin{bmatrix}a^2&0&a^2\\0&a^2&0\\0&0&a^2\end{bmatrix}$ $= \begin{bmatrix}1-a^2&0&a-a^2\\0&1-a^2&0\\0&0&1-a^2\end{bmatrix}$.

Since $D-CA^{-1}B$ is upper-triangular, its determinant is simply the product of the diagonal elements, i.e. $\det(D-CA^{-1}B) = (1-a^2)^3$.

Therefore, $\det \begin{bmatrix}A&B\\C&D\end{bmatrix} = \det(A)\det(D-CA^{-1}B) = 1 \cdot (1-a^2)^3 = (1-a^2)^3$.

share|cite|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.